An Amish wedding - Long, Kelly; Fuller, Kathleen; Wiseman, Beth, 1962- (Waterville, Maine : Thorndike Press, 2012)
A collection of three novellas about three different couples at an Amish wedding includes Beth Wiseman's "A Perfect Plan," in which Priscilla King wonders if her wedding to Chester Lapp will come off after a series of problems.
A perfect secret / Kelly Long -- A perfect match / Kathleen Fuller -- A perfect plan / Beth Wiseman.
Keywords: Amish -- Fiction; Weddings -- Fiction; Christian fiction